The biomechanical demands of snowboard landings in training with elite freestyle snowboard athletes - Noonan, J. M. (John Moores University, 2018)
Freestyle snowsport has emerged as one of the fastest growing Winter Olympic sports in the past decade, despite this no countries/teams have published data explaining the sports biomechanical demands in training or competition. Information describing the kinetic, kinematic and muscular demands relative to jump landing actions has not been investigated with elite freestyle athletes. Data were collected from athletes of the Great Britain Park and Pipe team during an official team training session, conducted on an artificial landing slope. Five athletes were assessed over multiple trials in three jump landings completed in regular, switch, 360 degree (deg) rotation jump landings. Measures including; landing acceleration (g), knee flexion angle (deg), knee angular velocity (d/sec) and integrated electromyography (iEMG) in muscles of the upper-thigh (bicep femoris, rectus femoris, semitendinosus, vastus lateralis, and vastus medialis), in pre and post-initial contact (IC) phases of jump landings were recorded. Large peak board accelerations were found in the regular and 360 deg rotation jump landing conditions, which corresponded with increased knee flexion angle and knee angular velocity at the point of initial contact (landing) and post-IC phase. Group summed mean iEMG revealed higher overall muscle activation post-IC versus pre- IC, and higher mean iEMG and peak % MVC recorded in the BF, RF, VL and VM muscles post-IC in the 360 deg rotation condition. Highest mean iEMG in the ST muscle was found post-IC in the regular jump landing condition. Elevated preactivation of hamstring (BF, ST) muscles was found in switch and 360 deg rotation conditions. And, higher mean and peak iEMG values were also observed post-IC in the quadricep (RF, VL and VM) muscles. This research can be used to inform practitioners of the biomechanical demands of snowboard jump landings, which is currently absent from the scientific literature. More specifically, the findings reveal the importance high muscular strength and rate of force development capabilities of hamstring and quadricep muscles, which should be targeted in athletic development programmes to assist lower-limb performance during snowboard landings.